A Linguistic Landscape in a Thailand Chinatown Area - Enggar Setyo Rini; Khristianto; Arif Budiman (ELITE Association Indonesia, 2023)
ABSTRACTThis is to reveal the language displayed at a street in a Chinatown area, Thailand. This study employed a qualitative descriptive method; it is to describe the conditions or phenomena. The data were taken from a Google Streetview application in Chinatown, Thailand. The data were analysed in terms the language(s) used and the sources of the signages. Based on the analysis, the signs in the area can be divided into three types: monolingual, bilingual, and trilingual. The languages displayed in monolingual signs are : Thai, and English. Meanwhile in bilingual signs, the language pairs employed are Thai-English, and, Thai-Chinese. Finally, trilingual signs show the trios of Thai-English-Japanese, and Thai-Chinese-English. In terms of their sources, all the monolingual signs are private signs, meaning they were made by non-governmental agencies. They are from the business institution. Most bilingual signs are public signs or top-down signs, made by the governmental agencies. Some others are displayed by private sectors. Finally, all the signs made in trilingual are bottom-up. All of them are shops signs displaying their products to cover a wide catch. Keywords: shop signs, Chinatown, sign, bottom-up signs, top-down signs, bilingual, multilingual.